Quick Assessment of Bridge Performance Based on Dynamic Parameters Acquired with Smartphone Application - Khoeri, Heri; Nugroho, Panji; Pradana, Roberto (Clean Energy and Smart Technology, 2024)
The road management regulation aims to achieve reliable and excellent road services that prioritize the interests of the community by ensuring the functional and competitive performance of the roads, as well as community participation in road management in accordance with Republic of Indonesia Law No. 2 of 2022. As part of the community, when crossing the Tegineneng Bridge on the Tegineneng-Sp. Tanjung Karang road section in Lampung Province and feeling discomfort from the bridge vibrations, participating individuals conducted vibration measurements using 2 smartphones. The gyroscopes in the smartphones, packaged within a g-force application, were capable of recording real-time vibrations in a user-friendly manner, and the output data was compatible with existing modal analysis software. Subsequently, vibration data recordings using the SSI algorithm yielded dynamic parameters such as a natural frequency of 2.009Hz and a damping ratio of 7.927%. The frequency of 2.009Hz for a span of 60m is lower compared to bridges of the same span from the dynamic bridge test regression equation in Indonesia, which is 2.347Hz. Under these conditions, it is estimated that the Tegineneng Bridge experienced minor structural damage with a damage level of 14.1% and its capacity is lower by 28.2% than the empirical estimate. The damping ratio exceeding 5% is estimated to be due to excessive energy dissipation through cracks in the concrete or through defects in the connections between steel frame elements. It is recommended that relevant stakeholders conduct a detailed inspection of the bridge to ensure its safety and undertake necessary measures to guarantee the safety of its users.